An eastern Congolian endemic, or widespread but secretive? New data on the recently described Afrixalus lacustris (Anura, Hyperoliidae) from the Democratic Republic of the Congo - Tadeáš Nečas; Gabriel Badjedjea; Janis Czurda; Václav Gvoždík (ZooKeys)
The Great Lakes spiny reed frog (Afrixalus lacustris) was recently described from transitional (submontane) forests at mid-elevations of the Albertine Rift mountains in the eastern Congolian region. Previously, because of its similarity, it had been understood to represent eastern populations of the unrelated A. laevis, which is known mainly from Cameroon. Based on DNA barcoding, we document the westward extension of the known range of A. lacustris within lowland rainforests in the Northeastern and Central Congolian Lowland Forests. One sample was represented by a larva found in a clutch in a folded leaf, a typical oviposition type for most Afrixalus species, contrary to oviposition on an unfolded leaf surface in the similar A. laevis and closely related A. dorsimaculatus and A. uluguruensis. Comparison of the advertisement call of A. lacustris from Salonga National Park, Democratic Republic of the Congo, indicates similarity to its sister species from montane areas of the Albertine Rift, the ghost spiny reed frog (A. phantasma). Phylogeographic analysis suggests that A. phantasma and A. lacustris speciated allopatrically during the Early Pleistocene, with the former having refugia in montane forests and the latter in transitional and also lowland forests. The lowland populations of A. lacustris represent distinct evolutionary lineages, which diversified probably in isolated forest refugia during the Middle Pleistocene.